Application of Information Systems at PT Angkasa Pura II Silangit Airport - Ayu Kurnia Sari; Hendra Saputra; Ku Halim Bin Ku Ariffin (Ridwan Institute, 2023)
PT Angkasa Pura II (Persero) is one of the State-owned Enterprises engaged in the business of airport services and services linked to the air city. The purpose of the research is to analyze the accounting data system at PT. Angkasa Pura II Silangit. This research uses descriptive research methods. From the results of this research, it can be seen that the accounting data system presented by the industry is stored and recorded in SAP. Strandar is used to view code in processing and inputting every transaction contained in industrial activities. PT. Angkasa Pura already has a very complete accounting data system, this system can be connected to all components of central and branch activities. In manual use, this system has been designed very well but must be checked and memorized in use with SAP that has been available. Employees cannot use the system carelessly and the code must also be able to be adjusted properly.